Microscopic evolution of dielectric nanoparticles at different calcination temperatures synthesized via sol-gel auto-combustion - Adil, M. (American Institute of Physics Inc., 2015)
Dielectric nano powder synthesis is carried by a simple and fast sol-gel auto-combustion method. The transformation of crystalline phases of as-synthesized nano powders is investigated through the detailed transmission electron microscopy (TEM), revealed the crystallographic alterations and morphological information even at lattice scale. From specific area electron diffraction (SAED) pattern, has specified the d-spacing and corresponding planes supported by the observed lattice fringes. The morphological characterization of nanoparticles is performed through field-emission scanning electron microscopy (FESEM), exhibiting the increment in particle size due to agglomeration with the increase in annealing temperature. Furthermore, EDX pattern has been used to verify the formation of nanoparticles by revealing the presence of required elements. Â© 2015 AIP Publishing LLC.